Mosquitoes (Diptera : Culicidae) of Singapore : updated checklist and new records - Lam-Phua, Sai-Gek (2020)
Prior to 1965, Singapore was part of the Malaya (now Malaysia) and was usually not mentioned when mosquito records were reported for Malaya. Consequently, many species that occurred in Singapore were not listed in the world mosquito catalog, and the available checklist for Singapore since 1986 is incomplete, with some imprecise species information. In updating this checklist, we examined and verified mosquito specimens collected from Singapore in various depositories, including a thorough review of past taxonomic literature. Here, we report a checklist of 182 mosquito species, 33 new distribution records, and a consolidated status list of vectors for Singapore. As Singapore is a travel hub and hosts one of the busiest container ports in the world, there is a risk of introducing mosquito species and their associated pathogens of human disease to the country. Hence, the distribution records are important to increase our knowledge on mosquito ecology as well as to understand the risk of newly introduced vectors and their associated pathogens.